Banks and German Corporate Governance: On the Way to a Capital Market-Based System? - Andreas Hackethal; Reinhard H. Schmidt; Marcel Tyrell (Johann Wolfgang Goethe-Universität Frankfurt am Main, Fachbereich Wirtschaftswissenschaften, 2005)
The German corporate governance system has long been cited as the standard example of an insider-controlled and stakeholder-oriented system. We argue that despite important reforms and substantial changes of individual elements of the German corporate governance system the main characteristics of the traditional German system as a whole are still in place. However, in our opinion the changing role of the big universal banks in the governance undermines the stability of the corporate governance system in Germany. Therefore a breakdown of the traditional system leading to a control vacuum or a fundamental change to a capital market-based system could be in the offing.
Keywords: G34; G32; G38; 330; Corporate governance; banking system; co-determination; board of directors; complementarity; financial system; Corporate Governance; Eigentümerstruktur; Universalbank; Finanzmarkt; Mitbestimmung; Deutschland